Strategic Planning for Investing in Mineral Resources in Anbar Governorate Using SWOC Analysis - Firas Ata Alkubaisy*, Husam; Fadel Jawad Al-Dahlaki, Saja (Journal of Economics and Administrative Sciences, 2024)
Purpose: The study aims to find the appropriate strategy to activate the role of mineral investment in achieving economic and social development in Anbar Governorate, and to identify the obstacles that prevent this through analyzing the internal and external environments that include strengths, weaknesses, opportunities, and challenges. Theoretical Framework: Mineral wealth is one of the most important natural resources in our world. Its discovery and exploitation contribute to the development, growth, and advancement of economies globally, which positively impacts various aspects of economic, social, and political life. It is noteworthy that Iraq in general, and Anbar province in particular, possess a rich environment abundant in mineral resources distinguished by their quantity and economic variety. Design/Methodology/Approach : The research relied on the inductive approach by analyzing data from official sources, as well as personal interviews with academics and officials in positions of responsibility in Anbar Governorate and directors of departments related to mining investment, and after relying on the results of the checklists in the tables included in the research (2, 3, 4, and 5) for the sample consisting of 25 people, in addition to using the strategic matrix (SWOC) to develop a future strategic plan to exploit the mineral resources available in Anbar Governorate. Findings: The comparison of the results obtained through the strategic analysis using the SWOC method with the main research hypothesis revealed the extent of convergence between the results and the hypothesis, which suggests an abundance of mineral resources alongside obstacles hindering their exploitation. Additionally, there is a lack of a clear and specific strategy for mineral investment in the province. Research, Practical & Social Implications: The researchers propose a future research agenda, emphasizing the necessity of conducting further studies that address the strategic analysis of natural resources in Anbar Province. Originality/Value: The results indicate that the three strategies developmental, remedial, and defensive are difficult to implement in the province’s economy, as shown by the numerical results of the SWOC matrix. The contractionary strategy appears to be the most suitable, as it applies to economies facing economic crises, that need to narrow the gap in their economic performance and rehabilitate their basic economic structure.